The Effect of English Reading Based on Embedded Sensor System on the Cultivation of College Students' Humanistic Spirit. (29th March 2022) - Cui, Limin; Zhang, Jiangnan; Zhang, Yuai
Abstract : In order to better improve the cultivation goal of college students' humanistic spirit, this paper puts forward the research on the role of English reading based on embedded sensor system in the cultivation of college students' humanistic spirit. Embedded sensor system is used to carry out college English reading teaching in the humanistic teaching content in the teaching process. In addition, the evaluation index of college students' English reading humanistic spirit cultivation is constructed, in order to achieve the goal of improving English reading teaching and task spirit training.